Bifurcation and degradation of geomaterials in the new millennium : proceedings of the 10th International Workshop on Bifurcation and Degradation in Geomaterials /: proceedings of the 10th International Workshop on Bifurcation and Degradation in Geomaterials. (2015) - Unknown
No abstract available